Why the World Trade Organization is Critical for Vaccine Supply Chain Resilience During a Pandemic - Bown, Chad P. (World Bank, Washington, DC, 2022)
Cross-border supply chains and international trade played a critical role in vaccinating much of the world to address the Coronavirus (COVID-19) pandemic. Considering that experience, this note describes the changes needed to make the World Trade Organization (WTO) a more useful institution during such a public health emergency. It begins by describing the market failures confronting vaccines especially on the supply side, to introduce the domestic subsidies and contracting arrangements needed to accelerate vaccine research and development, and to increase the scale and speed of vaccine production during a pandemic. As an application, it relies on illustrative examples of US subsidies that emerged during COVID-19. However, the challenge confronting policymakers is exacerbated in an environment characterized by cross-border supply chains, making input shortage problems impacting production even worse. Thus, the note highlights the need for new forms of international policy coordination, including initiatives on supply chain transparency, as well as agreements to increase subsidies across countries to jointly scale up vaccine output and input production capacity along the entire supply chain. It concludes that while the WTO was mostly absent this time around, it remains the best-positioned international organization to facilitate these novel forms of international economic policy cooperation.